2016
DOI: 10.1080/02640414.2016.1221522
|View full text |Cite
|
Sign up to set email alerts
|

Exercise does not increase salivary lymphocytes, monocytes, or granulocytes, but does increase salivary lysozyme

Abstract: An increase in salivary leukocytes may contribute to the exercise-induced increase in salivary antimicrobial proteins (AMPs). However, exercise-induced changes in salivary leukocytes have not been studied. The purpose of the study was to describe salivary leukocyte changes with exercise. Participants (n = 11, 20.3 ± 0.8 years, 57.2 ± 7.6 ml kg min peak oxygen uptake ((VO) ̇peak), 11.1 ± 3.9% body fat) ran for 45 min at 75% of VO. Stimulated saliva (12 mL) was collected pre- and immediately post exercise. Saliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
6
1
1
Order By: Relevance
“…A previous study on elite rowers (30) also observed no significant change in salivary lysozyme concentrations in response to exercise. This finding was inconsistent with that of some previous studies (31)(32)(33)(34), which found an increase in salivary lysozyme secretion following exercise. In these studies, lysozyme responses increased significantly with moderate exercise intensity and increased further with high-intensity exercise (35).…”
Section: Salivary Lysozyme Concentrationcontrasting
confidence: 99%
“…A previous study on elite rowers (30) also observed no significant change in salivary lysozyme concentrations in response to exercise. This finding was inconsistent with that of some previous studies (31)(32)(33)(34), which found an increase in salivary lysozyme secretion following exercise. In these studies, lysozyme responses increased significantly with moderate exercise intensity and increased further with high-intensity exercise (35).…”
Section: Salivary Lysozyme Concentrationcontrasting
confidence: 99%
“…Regarding the cellular origin of the CD24 + EVs, saliva of healthy human individuals is known to contain granulocytes . When we labeled cells in saliva with anti‐CD66b, a major cell population stained for this granulocyte marker (Figure S3A–C).…”
Section: Discussionmentioning
confidence: 99%
“…Gillum et al also demonstrated that overproduction of leukocytes in saliva is not necessary to increase the amount of lysozyme [ 97 ]. Kim et al determined the effect of xylitol and sorbitol on lysozyme activity.…”
Section: Determination Of Enzymesmentioning
confidence: 99%